Differences in Cardiopulmonary Fitness Between Boy and Girls With Repaired Tetralogy of Fallot - Chang, Yung-Liang; Kuan, Tzu-Hsuan; Chen, Chia-Hsin; Tsai, Yi-Ju; Chen, Guan-Bo; Lin, Ko-Long; Tuan, Sheng-Hui (Frontiers in Pediatrics, 2022)
Objective: Many studies have demonstrated that patients with repaired tetralogy of Fallot (rTOF) have generally poorer cardiopulmonary fitness (CPF). However, little knowledge about how the disease would lead to different CPF in each sex. Therefore, this study aimed to investigate whether sex differences affect CPF in children and adolescents with rTOF. Methods: This retrospective study recruited patients with rTOF after acute stage receiving cardiopulmonary exercise testing (CPET) in recent 10 years. CPF was determined by symptom-limited CPET with treadmill under ramped Bruce protocol. Boys and girls were categorized into groups based on body mass index (BMI) and fat mass index (FMI). The BMI was grouped by Taiwanese obesity cutoff points. The FMI was categorized by the body fat percentage. Excess adiposity was defined as (1) “overweight” and “obesity” by BMI and (2) greater than the sex- and age-specific 75th percentile of whole subjects by FMI. Results: A total of 185 participants (104 boys and 81 girls) with rTOF were recruited for the final analysis. With the BMI category, 76 boys and 63 girls were in the normal group, whereas 28 boys and 18 girls were in the excessive adiposity group. With the FMI category, 77 boys and 60 girls were in the normal group, whereas 27 boys and 21 girls were in the excessive adiposity group. The analysis of the body composition of rTOF subjects showed that there was no statistically significant difference between subgroups of two genders, but both showed a smaller body size than normal Taiwanese children. When comparing the CPF among subjects with different BMI or FMI groups, the patients in the excessive adiposity group had significantly lower values in metabolic equivalents (MET) at anaerobic threshold, peak MET, and measured peak oxygen consumption (VO2) to predicted peak VO2 (), regardless of sex. Moreover, boys (60.90%) presented poorer CPF than girls (74.22%, p < 0.001). Conclusion: In Taiwan, patients with rTOF had poorer CPF than healthy peers. Girls with rTOF have better CPF than boys with rTOF. The effect of gender stereotype on sports participation and self-efficacy might be one of the contributing factors.